2005
DOI: 10.4049/jimmunol.174.10.6054
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin (PTX) B Subunit and the Nontoxic PTX Mutant PT9K/129G Inhibit Tat-Induced TGF-β Production by NK Cells and TGF-β-Mediated NK Cell Apoptosis

Abstract: We show that the pertussis toxin B oligomer (PTX-B), and the PTX mutant PT9K/129G, which is safely administered in vivo, inhibit both transcription and secretion of TGF-β elicited by HIV-1 Tat in NK cells. Tat-induced TGF-β mRNA synthesis is also blocked by the ERK1 inhibitor PD98059, suggesting that ERK1 is needed for TGF-β production. Moreover, Tat strongly activates the c-Jun component of the multimolecular complex AP-1, whereas TGF-β triggers c-Fos and c-Jun. Of note, treatment of NK cells with PTX-B or PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…These results support the hypothesis that PTX-B or related molecules, such as the genetically modified PT-9K/129G (83), which retains all the HIV inhibitory features of PTX-B (9,26,84), could represent potent new pharmacological agents against HIV infection, as we have also recently demonstrated in infected lymphoid histocultures (85) and hu-PBL SCID mice infected with HIV (86).…”
Section: Discussionsupporting
confidence: 73%
“…These results support the hypothesis that PTX-B or related molecules, such as the genetically modified PT-9K/129G (83), which retains all the HIV inhibitory features of PTX-B (9,26,84), could represent potent new pharmacological agents against HIV infection, as we have also recently demonstrated in infected lymphoid histocultures (85) and hu-PBL SCID mice infected with HIV (86).…”
Section: Discussionsupporting
confidence: 73%
“…Regulatory feedback at IRIS onset may be exerted either by regulatory T cells or by subsets of NK cells secreting anti-inflammatory cytokines such as IL-10 and TGF-␤. 29,30 IL10-producing NK cells could suppress specific T-cell responses, 31 thereby controlling exaggerated responses during TB-IRIS. 23 IL10 and TGF-␤ are also able to down-regulate NK cell-activating receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Tat has been shown to interact with some G-coupled protein receptors. as chemokine receptors (57), and several reports have shown that some of the activities of extracellular Tat including neurotoxic ones in astrocytes are blocked by PTx (58,59). The characterization of the putative Tat receptor deserves further studies.…”
Section: Discussionmentioning
confidence: 99%